PENERAPAN 5S DALAM PENINGKATAN KERJA ORGANISASI PENDIDIKAN - Mhd Lutfi Wijaya; Shohiron Shohiron (Jurnal Manajemen Pendidikan, 2026)
This study examines the application of the 5S method (Seiri/Sort, Seiton/Set in Order, Seiso/Shine, Seiketsu/Standardize, Shitsuke/Sustain) as a strategy to improve organizational performance in educational institutions. By integrating a review of recent literature (including studies conducted in educational settings) and a practical implementation framework, this research explains how 5S can be applied in school or higher education environments to achieve greater efficiency, organization, and a more productive work culture. The results of the review indicate that the implementation of 5S leads to: (1) more orderly facilities and administrative processes with faster access; (2) increased motivation and job satisfaction among teaching staff and administrative personnel; (3) heightened awareness of safety and orderliness in the learning environment; and (4) a reduction in wasted time caused by searching for documents or unstructured workflows. However, the implementation of 5S in the educational context also faces challenges such as resistance to cultural change, limited resources, and difficulties in sustaining the program over time. To address these challenges, this study recommends strong commitment from school leadership, regular training and coaching, periodic 5S monitoring and audits, and a simple reward system for school units that achieve a high level of 5S discipline.